2022
DOI: 10.1159/000526346
|View full text |Cite
|
Sign up to set email alerts
|

A Gene Signature Comprising Seven Pyroptosis-Related Genes Predicts Prognosis in Pediatric Patients with Acute Myeloid Leukemia

Abstract: Introduction: To construct a pyroptosis-related risk score (RS) model for the prognosis of acute myeloid leukemia (AML). Methods: The TARGET (training) and E-MTAB-1216 (validation) datasets were downloaded. Pyroptosis-related genes with differences in expression were identified between the recurrent and non-recurrent samples of the training dataset. An RS prognostic model comprising seven pyroptosis-related genes was constructed using LASSO regression coefficients. The samples were classified into the high- an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…Accumulating evidences indicated that chronic inflammation in tumor microenvironment (TME) played a major role in immune invasion, thus contributing to tumorigenesis (Grivennikov et al, 2010;Shin and Brusselle, 2014; Frontiers in Genetics frontiersin.org Lu et al, 2021). In some studies of pyroptosis in AML, TME was found remarkably different between risk groups (He et al, 2022;Shao et al, 2022;Zhou et al, 2022). Pyroptosis, an inflammationdependent form of PCD, was proved to participate in tumor growth and chemosensitivity (Xia et al, 2019), while its mechanisms are complicated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accumulating evidences indicated that chronic inflammation in tumor microenvironment (TME) played a major role in immune invasion, thus contributing to tumorigenesis (Grivennikov et al, 2010;Shin and Brusselle, 2014; Frontiers in Genetics frontiersin.org Lu et al, 2021). In some studies of pyroptosis in AML, TME was found remarkably different between risk groups (He et al, 2022;Shao et al, 2022;Zhou et al, 2022). Pyroptosis, an inflammationdependent form of PCD, was proved to participate in tumor growth and chemosensitivity (Xia et al, 2019), while its mechanisms are complicated.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested the high-risk group of pyroptosis-related signature was enriched in immunosuppressive cells and had lower drug sensitivity to classical chemotherapy ( Pan et al, 2022 ; Shao et al, 2022 ; Zhou et al, 2022 ). In pediatric patients with AML, PRGs were found to predict recurrence ( He et al, 2022 ). To probe the underlying mechanisms further of our signature, the TME and enrichment analysis between risk subgroups were investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the mechanisms of regulated AML cell death and their modulation/regulation by V-ATPase need further characterization [4,5]. Several forms of programmed cell death may be operative in human AML [118][119][120][121][122][123][124][125][126][127][128][129][130][131], including endoplasmic reticulum stress-induced apoptosis [69]; possibly autophagy-associated apoptosis, although autophagy is generally regarded as a survival mechanism [120]; ferroptosis due to lethal iron accumulation [5,[118][119][120][121][122][123][124]; inflammatory necroptosis [124][125][126][127] and pyroptosis [128,129]; oncosis [130]; apoptosis-like anoikis due to loss of cell anchorage [5,131]; and pH-dependent alkaliptosis [5]. Thus, programmed cell death in AML cells can have a mixed etiology, including apoptosis (which seems particularly important), together with other forms of programmed cell death.…”
Section: Discussionmentioning
confidence: 99%